2021
DOI: 10.1177/10436596211039553
|View full text |Cite
|
Sign up to set email alerts
|

Technical Meets Traditional: Language, Culture, and the Challenges Faced by Hmong Medical Interpreters

Abstract: Introduction Ineffective intercultural communication can occur due to inaccurate medical interpreting for limited English proficiency (LEP) patients. Research shows that Hmong patients experience poorer quality interpreter services than other LEP populations. This study’s purpose is to understand Hmong medical interpreters’ perceptions of the factors that affect their ability to make accurate medical interpretations during clinical encounters. Method A qualitative study was conducted with Hmong-speaking medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Interpreters' descriptions of their professional experiences overall, as well as their experience interpreting for the CHARM study, add to a growing body of research that explores interpreters' perspectives on their role and their experiences in practice (Lor et al, 2022; Price et al, 2012), including in genetic counseling (Lara‐Otero et al, 2019). Some research has identified a preference for in‐person interpretation by both GCs and interpreters (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interpreters' descriptions of their professional experiences overall, as well as their experience interpreting for the CHARM study, add to a growing body of research that explores interpreters' perspectives on their role and their experiences in practice (Lor et al, 2022; Price et al, 2012), including in genetic counseling (Lara‐Otero et al, 2019). Some research has identified a preference for in‐person interpretation by both GCs and interpreters (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that LEP Hmong patients, interpreters, and providers have difficulty understanding each other due to Hmong patients' use of pain metaphors, which are incompatible with the language and culture of interpreters and providers [ 5 , 7 , 8 ]. This impairs providers' ability to diagnose and manage pain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%